Sexual harassment and turnover intention at the workplace: a case study at Melaka Chief Minister Department / Farah Wahida Mohd Rafly and Fatin Fazrida Peros Khan - Mohd Rafly, Farah Wahida; Peros Khan, Fatin Fazrida (Faculty of Administrative Science and Policy Studies, 2012)
This research is about “A study on sexual harassment and turnover intention: A case study at Melaka Chief Minister Department. Stratified sampling by disproportionate of 92 respondents were the employees from 10 (10) different departments of Melaka Chief Minister Department. All the 92 respondents have cooperatively answered the questionnaire distributed by the researchers. The objective of this research is first to identify the most influential factor that leads to sexual harassment among employees at Melaka Chief Minister Department. Second objective of this research is to identify the reasons employees involved in sexual harassment at the workplace and finally this research is to identify the relationship between sexual harassment towards turnover intention. There are four factors of sexual harassment which are socialization, cultural differences, moral values of the employees and also organization environment. These factors as independent variables while turnover intention as the dependent variable on this study. The most influential factor that leads to sexual harassment in this study was moral values of the employees and moral values of the employees shows weak relationship towards turnover intention at the workplace. This is due to the result of regression and correlation analysis that have been used. The reasons employees involved in sexual harassment was mostly because the victims of sexual harassment is reluctant to make a report regarding the case. Other reasons that encouraged the employees involved in sexual harassment were lack of effort of the top management to take action regarding cases that have been reported, sexual addiction of the employees and also affairs and workplace relationships. This is due to the result of frequencies and percentages methods that have been used by the researchers. In conclusion, moral value of the employees was the most influential factor that leads to sexual harassment and only moral value of the employees has the relationship towards turnover intention at Melaka Chief Minister Department.